Academic Senate Minutes 2006-12-14 - Academic Senate:::::::::
Approval of agenda. English MA revision approved. Information item - Sick and Tired: a case study of faculty workload and health by Birch Moonwomon. Provost Report. Special Report: Fees in Trust. Sabbatical policy amended and postponed to next meeting. EPC recommendation re: post-grad and unclassified grad student admission first reading. Endorsement of Statewide Senate Resolution on Cornerstones approved. Endorsement of Statewide Resolution on ACR 73 tabled.